Rare Earth Element - Edgar Alfonso Orjuela, Jose (IntechOpen, 2017)
Rare earth elements have significant physical and chemical properties, which have been made indispensable in many magnetic, electronic, and optical applications. For instance, rare earth magnets have high magnetic intensity that can be retained at high temperatures, making them ideal for aerospace applications. Moreover, rare earth elements allow to fabricate faster, smaller, and lighter devices such as cell phones and hard drives. They are also important for in-ear headphones, microphones, loudspeakers, optical fibers, smartphones, and tablet computers. All these technological possibilities have made sure that the rare earth elements are part of the daily life. Therefore, this book has a main objective to let the readers know useful information about the rare earth elements that possibly allow development of the researches in different fields of science where the rare earth elements are used.